Monitoring of Auditory Function in Newborns of Women Infected by SARS-CoV-2 during Pregnancy - Enrico Apa; Maria Teresa Presutti; Cecilia Rossi; Maria Federica Roversi; Salvatore Neri; Giancarlo Gargano; Giovanni Bianchin; Valeria Polizzi; Valeria Caragli; Daniele Monzani; Alberto Berardi; Silvia Palma; et al. (MDPI AG, 2023)
Background: Gestational SARS-CoV-2 infection can impact maternal and neonatal health. The virus has also been reported to cause newborn sensorineural hearing loss, but its consequences for the auditory system are not fully understood. Objective: The aim of this study was to evaluate the impact of maternal SARS-CoV-2 infection during pregnancy on newborn' hearing function during the first year of life. Methods: An observational study was conducted from 1 November 2020 to 30 November 2021 at University Modena Hospital. All newborns whose mother had been infected by SARS-CoV-2 during pregnancy were enrolled and underwent audiological evaluation at birth and at 1 year of age. Results: A total of 119 neonates were born from mothers infected by SARS-CoV-2 during pregnancy. At birth, five newborns (4.2%) presented an increased threshold of ABR (Auditory Brainstem Evoked Response), but the results were confirmed only in 1.6% of cases, when repeated 1 month later, while the ABR thresholds in all other children returned to normal limits. At the 1-year follow-up, no cases of moderate or severe hearing loss were observed, while concomitant disorders of the middle ear were frequently observed. Conclusions: Maternal SARS-CoV-2 infection, regardless of the trimester in which it was contracted, appears not to induce moderate or severe hearing loss in infants. It is important to clarify the possible effect of the virus on late-onset hearing loss and future research is needed.